Prevalencia de recesión gingival en pacientes de 18 a 50 años atendidos en la clínica odontológica de la UDLA - Márquez Ríos, María Gracia (2018)
It was possible to identify the prevalence of gingival recession (according to the classification of Miller and Pini-Prato) in patients 18 to 50 years treated at the Dental Clinic of the UDLA. The study population consisted of patients with gingival recession in the period from May to June 2016. This study evaluated 66 patients randomly chosen. They were only observed the posterior inferior parts and periodontal biotype, Miller classification and Pini Prato, amount of keratinized gingiva and percentage of biofilm was identified, among others. Furthermore catheterisation was performed parts and existing recession was observed. Of those surveyed men about 60% had thin periodontal biotype and 40% periodontal biotype thick. 90% of women had a thin periodontal biotype and only 10% have a thick periodontal biotype. Men had higher frequency of keratinized gingiva with a value of 3 and 4 mm in height for all its parts. While women had a lower frequency in several pieces. The percentage of biofilm men ranged from 88.8% and women ranged from 82.90%. Both men and women recession for most common piece Miller was the class I. In all parts have an incidence of about 80% of this class. Men surveyed had a higher ranking hegemony Pini Prato A- and B- for all its parts. Women surveyed had higher incidence of Pini Prato rated B-, followed by the A- rating. It was noted that the gingival recession is a multifactorial disease, which depends on more than one factor to manifest.